Economic growth, inequality and efficiency - Soňa Štikarová (University of Economics in Bratislava, Department of Economic Policy, 2014)
Over the last decades, theoretical work has come up with a significant amount of concepts how the income inequality and economic growth may affect each other. The recent literature identifies many channels through inequality may have positive, negative or even both effects on economic performance, but in different time dimensions. The relationship has been researched from the both perspective: the impact of income inequality on economic growth, and how the economic growth and efficiency are related to income inequality. Despite of the amount of theoretical and empirical work, the relationship between efficiency and equality is far from being well understood.
Keywords: E60; O10; 330; income inequality; efficiency; growth